Antifungal Activity of Benzoquinones Produced by Tribolium castaneum in Maize-Associated Fungi - Duarte, Sónia (2022)
Tribolium castaneum (Herbst) adults produce 1,4-benzoquinone (BQ), methyl-1,4-benzoquinone (MBQ), and ethyl-1,4-benzoquinone (EBQ). These components are chemical defenses used as repellents and irritants, and BQ has a negative impact on the growth of some fungal species. In this work, the inhibitory and/or lethal effects of these benzoquinones on the development of six fungi identified inmaize, namely Aspergillus flavus, A. fumigatus, A. niger, Fusarium sp., Penicillium sp., and Trichoderma sp., were evaluated. Ten-day-long disk diffusion trials were performed using benzoquinones. The experiments simulated the activity of BQ (B1) or “EBQ +MBQ” (B2) released by 40-day-old insect adults (n = 200), considering a total average release of 45 g per adult. Inhibition halos imposed by benzoquinones on fungal growth showed a significant effect when compared with the controls (water and solvent). Mycelial growth was decreased for all fungi, with the level of response depending on the fungal species. B1 and B2 displayed an inhibitory effect against all fungi, but Trichoderma sp. and A. niger showed rapid recoveries. B2 showed a lethal effect on Penicillium sp. The inhibitory and lethal activities of benzoquinones released by T. castaneum adults may contribute to regulate fungal growth, and understanding their interaction is important to develop innovative control strategies